Proceedings of international conference on advances in computing - R., Selvarani; Kumar, T V Suresh; Kumar M., Aswatha (Advances in Intelligent Systems and Computing, 2012)
This is the first International Conference on Advances in Computing (ICAdC-2012). The scope of the conference includes all the areas of Theoretical Computer Science, Systems and Software, and Intelligent Systems. Conference Proceedings is a culmination of research results, papers and the theory related to all the three major areas of computing, i.e., Theoretical Computer Science, Systems and Software, and Intelligent Systems. Helps budding researchers, graduates in the areas of Computer Science, Information science, Electronics, Telecommunication, Instrumentation, Networking to take forward their research work based on the reviewed results in the paper,  by mutual interaction through E-mail contacts in the proceedings.